2011
DOI: 10.1097/fpc.0b013e3283436b86
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and nongenetic factors associated with warfarin doserequirements in Egyptian patients

Abstract: Background and objective Warfarin is a commonly used oral anticoagulant with a narrow therapeutic index and various genetic and clinical factors that influence interpatient variability in dose requirements. This study investigated the impact of genetic and nongenetic factors on warfarin dose requirements in Egyptians. Methods DNA was extracted from 207 patients taking warfarin for more than 2 months and genotyped for VKORC1 (3673 G> A), CYP2C9 *2*3*4*5*8, CYP4F2 (V33M; rs2108622), APOE (rs429358, rs7412), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
81
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 24 publications
(31 reference statements)
16
81
1
Order By: Relevance
“…There is conflicting evidence on the association between warfarin doses and dietary factors such as alcohol and tea consumption, smoking and vitamin K intake. High intake of fat-soluble vitamin K theoretically diminishes the effect of warfarin, which interferes with coagulation by inhibiting regeneration of the reduced form of vitamin K. In our study, we did not observe a significant relationship between dietary factors (vitamin K intake, alcohol/tea consumption and smoking) and warfarin maintenance dose contrary to the findings in previous studies [30][31][32]. To investigate the association between dietary factors and warfarin dosage, more controlled studies are needed to achieve reliable results.…”
Section: Discussioncontrasting
confidence: 99%
“…There is conflicting evidence on the association between warfarin doses and dietary factors such as alcohol and tea consumption, smoking and vitamin K intake. High intake of fat-soluble vitamin K theoretically diminishes the effect of warfarin, which interferes with coagulation by inhibiting regeneration of the reduced form of vitamin K. In our study, we did not observe a significant relationship between dietary factors (vitamin K intake, alcohol/tea consumption and smoking) and warfarin maintenance dose contrary to the findings in previous studies [30][31][32]. To investigate the association between dietary factors and warfarin dosage, more controlled studies are needed to achieve reliable results.…”
Section: Discussioncontrasting
confidence: 99%
“…This variability in dose requirement could be attributed to the fact that carriers of the A allele haplotype (i.e., -1639 A) produce less VKORC1 than carriers of B allele haplotype (i.e., -1639 G) [19]. These data are in agreement with those reported by previous studies conducted in Egyptian population [17,18,20].…”
Section: Discussionsupporting
confidence: 90%
“…The stepwise selection method was used in multiple linear regression to evaluate the contribution of pVNTR-S, CYP2C9*2, and CYP2C9*3, to the warfarin dose requirement, using p Ͻ 0.2 and p Ͻ 0.05 as criteria for entering and staying in the model. Independent studies in whites (Aquilante et al, 2006), African Americans (Gage et al, 2004), Asians (Zhao et al, 2004), and Egyptians (Shahin et al, 2011) have confirmed that both CYP2C9*2 and *3 are functional variants that influence the warfarin dose required to maintain the therapeutic international normalized ratio. Therefore, we performed combined analysis in all the warfarin patients.…”
Section: Cyp2c9 Promoter Pvntr Polymorphism Regulates Gene Expressionmentioning
confidence: 97%
“…To test the clinical effect of the promotervariable number tandem repeat (pVNTR) polymorphism, we assessed the association of the pVNTR genotype with the maintenance warfarin dose required in patients undergoing stable warfarin anticoagulation therapy from the University of Florida (n ϭ 348) (Aquilante et al, 2006) and Cairo, Egypt (n ϭ 207) (Shahin et al, 2011). The relevant protocols were approved by the local institutional review boards.…”
Section: Cyp2c9 Promoter Pvntr Polymorphism Regulates Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation